Malarial drug targets cysteine proteases as hemoglobinases - Mokoena, Fortunate (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2012)
Malaria has consistently been rated as the worst parasitic disease in the world. This disease affects an estimated 5 billion households annually. Malaria has a high mortality rate leading to distorted socio-economic development of the world at large. The major challenge pertaining to malaria is its continuous and rapid spread together with the emergence of drug resistance in Plasmodium species (vector agent of the disease). For this reason, researchers throughout the world are following new leads for possible drug targets and therefore, investigating ways of curbing the spread of the disease. Cysteine proteases have emerged as potential antimalarial chemotherapeutic targets. These particular proteases are found in all living organisms, Plasmodium cysteine proteases are known to degrade host hemoglobin during the life cycle of the parasite within the human host. The main objective of this study was to use various in silico methods to analyze the hemoglobinase function of cysteine proteases in P. falciparum and P. vivax. Falcipain-2 (FP2) of P. falciparum is the best characterized of these enzymes, it is a validated drug target. Both the three-dimensional structures of FP2 and its close homologue falcipain-3 (FP3) have been solved by the experimental technique X-ray crystallography. However, the homologue falcipain-2 (FP2')' and orthologues from P.vivax vivapain-2 (VP2) and vivapain-3 (VP3) have yet to be elucidated by experimental techniques. In an effort to achieve the principal goal of the study, homology models of the protein structures not already elucidated by experimental methods (FP2', VP2 and VP3) were calculated using the well known spatial restraint program MODELLER. The derived models, FP2 and FP3 were docked to hemoglobin (their natural substrate). The protein-protein docking was done using the unbound docking program ZDOCK. The substrate-enzyme interactions were analyzed and amino acids involved in binding were observed. It is anticipated that the results obtained from the study will help focus inhibitor design for potential drugs against malaria. The residues found in both the P. falciparum and P. vivax cysteine proteases involved in hemoglobin binding have been identified and some of these are proposed to be the main focus for the design of a peptidomimetric inhibitor.
Keywords: Malaria -- Chemotherapy; Antimalarials; Hemoglobin; Proteolytic enzymes; Cysteine proteinases; Plasmodium falciparum; Plasmodium vivax; Papain